Variación espacio-temporal de nitratos en la microcuenca del Río Cutuchi utilizando técnicas de estimación geoestadística - Barba Oña, Francis Gabriela (2018)
The present study evaluated the spatio-temporal variation of the nitrate concentrations in the Cutuchi River Microbasin (RMC), which is part of the Pastaza River that originates in the badlands of the Cotopaxi volcano, has a basin area of 2677 km2 and an approximate length of 60 km. The contamination of the rivers by the concentration of nitrates affecting the agricultural crops and human health due to the presence in surface waters. For the research, two databases were used, one from the Technical University of Cotopaxi (UTC) and the other from the International SEK University, which were monitored from September 2010 to July 2011 by the UTC, and for the SEK from October to April 2017. Initially an exploratory data analysis (AED) was carried out, to evaluate the distribution and behavior of the data, later they were processed with the Surfer interpolator package and finally the maps of were made. Spatial distribution of nitrates in the MRC. Were made as a result, it was obtained in the AED that the data presented few outliers and completed with the criterion of the mean were interpolated to obtain the three best interpolators: moving averages, radial basis function and kriging for the two databases that were valued with the mean square error (EMC). It was concluded that through the best interpolators, nitrate data were obtained in the MRC, which were not monitored and to predict their distribution behavior, thus decreasing costs of time and money required for the collection of field information